THE EFFECT OF STATIC STRETCHING ON MUSCLE FLEXIBILITY IMPROVEMENT IN TAEKWONDO ATHLETES - Rasendria, Muhamad; Dede Rohmat Nurjaya; Sagitarius, Sagitarius; Mulyana (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study examines the impact of static stretching on flexibility improvement in Taekwondo athletes. Specifically, the purpose of the research is to observe the effects of implementing this method over 14 sessions (conducted three times per week). The research method used is an experimental design with a one-group pretest-posttest design. The sample in this study was selected using purposive sampling, consisting of 12 athletes. To measure flexibility, the study employed the Maximal Hip Flexion Activation Knee Extension (MHFAKE) test. Quantitative data were analyzed using the Wilcoxon test. The results show that static stretching significantly improves flexibility, with the average score increasing from 35.83 to 21.66 (50.00%). The Wilcoxon test indicated a p-value of 0.002 < 0.05, meaning the alternative hypothesis (Ha) is accepted, and there is a significant effect. In conclusion, static stretching has a significant impact on the improvement of flexibility in Taekwondo athletes' muscles.